Genetically exceptional?: women's experiences of being at risk of hereditary breast and ovarian cancer - Rowley, Emma (2005)
This thesis questions whether the experiences of women at-risk of hereditary breast and ovarian cancer (HBOC) might be genetically exceptional. Using a combination of retrospective in-depth interviews with women at-risk and observations of consultations carried out at a regional specialist centre, this research questions the genetic exceptionalism thesis and the argument that the experiences and decisions that women at-risk of HBOC make, are unique and thus different compared to those of women diagnosed with non-genetic, sporadically developing breast or ovarian cancer.